Latihan Renang Intensitas Berat Lebih Meningkatkan Kekuatan Daya Rentang - Utami, Yulian Wiji (Fakultas Kedokteran Universitas Brawijaya, 2009)
ABSTRACTThe objective of this study was to prove that light intensity and heavy intensity of swim training can improvewide area of cross section, amount of fibroblas cell and thick of sharpey's fibre at achiles tendon. This studyused separate sample pretest-posttest control group design, with experimental animals the white rat (Rattusnorvegicus strain Wistar) Male, age around 3 weeks, counted 28 tails. Two treatment type that given were (1)light intensity of swim training (with giving of burden 3% Body Weight) and (2) heavy intensity of swim training(with giving of burden 9% Body Weight). Data is analysis by descriptive statistic, MANOVA and deskriminantest with trust level of 95%. Result of study was showed light intensity of swim training and heavy intensity, tobe increasing of wide area of cross section, amount of fibroblas cell and thick of sharpey's fibre compare toposttest control. MANOVA test result to respon change of treatment effect which get that treatment givesignificant difference (Trace Holtelling's, p<0,05). From discriminant test result was showed variable amountof fibroblas cell and thick of sharpey's fibre showing that have significant contribution of change response oftreatment (p<0,05), while variable wide area of cross section not showed significant contribution have ameaning of response change of treatment effect ( p>0,05).Keywords: intensity of swim training, wide area of cross section, fibroblas cell, sharpey’s fibre.